2011
DOI: 10.1111/j.1439-0272.2010.01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flutamide and two novel synthetic steroids on GABA, glutamine and some oxidative stress markers in rat brain and prostate

Abstract: Flutamide is a steroid used to treat androgen-dependent disorders and as antiepileptic, but it induces a number of non-desirable side effects. This work was aimed at assaying the effect of flutamide and two novel synthetic steroids on the levels of GABA, glutamine and oxidative stress markers. Male Wistar rats (weight 180 g) received a single diazepam dose (5 mg/kg) 30 min prior to sacrifice (group A). Group B, flutamide; group C, 16β-methyl-17α-benzoyloxypregnen-4-en-3,20-dione; group D, estrone-3-hemisuccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This reduction may be associated with an interference in testicular androgenic capacity, since it was shown that patients with non-androgenic cancers showed reduction in serum testosterone levels, which was always linked to the individuals' metabolic status and hypogonadism (Fleishman et al, 2010). The L-glutamine supplementation did not increase the number of Leydig cells suggesting that this amino acid was not able to reduce a possible hormonal stress usually found in tumor situations, as observed in studies with testicular cancer and testicular toxicity, as well as hormonal disorders in organs with endocrine activity, such as prostate and others (Calderón Guzmán et al, 2011;Olaniyi et al, 2020;Rotovnik Kozjek et al, 2017)…”
Section: Intertubular Morphometrymentioning
confidence: 89%
“…This reduction may be associated with an interference in testicular androgenic capacity, since it was shown that patients with non-androgenic cancers showed reduction in serum testosterone levels, which was always linked to the individuals' metabolic status and hypogonadism (Fleishman et al, 2010). The L-glutamine supplementation did not increase the number of Leydig cells suggesting that this amino acid was not able to reduce a possible hormonal stress usually found in tumor situations, as observed in studies with testicular cancer and testicular toxicity, as well as hormonal disorders in organs with endocrine activity, such as prostate and others (Calderón Guzmán et al, 2011;Olaniyi et al, 2020;Rotovnik Kozjek et al, 2017)…”
Section: Intertubular Morphometrymentioning
confidence: 89%